Uma análise da geração e distribuição da riqueza das empresas do setor elétrico brasileiro listadas na base de dados do laboratório de finanças e risco da FEA/USP dos anos de 2010 a 2018 - Lopes, Renato Cezar de Paiva (2019)
The present study aims to analyze the correlation between the added value/benefit through the generated wealth and distributed by the companies in the electric segment listed on FEA/USP Finance and Risk Laboratory and the Gross Domestic Product of the states where those companies have their headquarters. The analyze of the data occurred between the years 2010 to 2018 through the correlation of the variables Total Added Value, Taxes and Duties (state) and the GPD. There is also been made a descriptive analyze about the power/electric scenario of the country’s 32 companies listed on the database according to the financial reports released between the period of 2010 to 2018. The analyze of the companies and the GPD is made by using IBM SPSS Statistics® software verifying through Pearson’s correlation if there is a relationship among the variables. For the procedure, each company listed composes the sample, excluding their respective holdings to prevent double counting of the values effectively distributed, where it verifies the relationship of total value added by the companies with the GPD. It concludes that there is a very strong correlation within the variables, which has a P value of 0,998. Because of the familiarity and proximity of the calculus of both GPD and the Added Value Statement there was an expectation about the correlation being positive in the results. From the analyzed data obtained from the Statement of Value Added, it shows that a relevant part of the value added distributed goes to taxes and duties, being an average of 61.59%. The smaller percentage goes to the employees with a percentage average of 9.63%. It is also possible to verify the companies’ capacity of generating wealth throughout the years.